Cohomology of fiber-bunched twisted cocycles over hyperbolic systems. Issue 3 (21st August 2020) - Backes, Lucas
Abstract: A twisted cocycle taking values on a Lie group G is a cocycle that is twisted by an automorphism of G in each step. In the case where G = GL ( d, ℝ), we prove that if two Hölder continuous twisted cocycles satisfying the so-called fiber-bunching condition have the same periodic data then they are cohomologous.